Inpatient Nurses' Perception of Workplace Violence Based on Specialty. (October 2020) - Perkins, Morgan; Wood, Leslie; Soler, Thaisha; Walker, Kimberly; Morata, Lauren; Novotny, April; Estep, Han
Abstract : OBJECTIVE: The aim of this study was to evaluate the impact of inpatient nursing specialties on the perceptions of workplace violence. BACKGROUND: The association between nursing specialty and the perception of workplace violence has not been identified. METHODS: An evaluation of inpatient nurses' perceptions of workplace violence at a single health system was conducted using a modified Survey of Violence Experienced by Staff instrument. RESULTS: Of the respondents, 87.2% experienced workplace violence, of which 96.3% was patient related. Patient-initiated verbal abuse, threats, and physical assault frequency differed significantly based on specialty. Post hoc comparisons further elucidate the differences in specialty populations. CONCLUSION: Workplace violence is a nursing concern; however, the frequency in which workplace violence occurs differs based on specialty. The frequency of threats and injuries to nursing staff was significantly higher in medical and trauma units.